Conservation and biodiversity monitoring in the tropics: realities, priorities and distraction - Sheil, Douglas (2001)
Monitoring and research activities may hinder rather than improce conservation in tropical countries. This paper identifies some critical threats to biodiversity and the limited resources for defending against them. It suggests various contributory factors, and a few common sense options for improved practice. It concluded that there is limited capacity for conservation in many countries and resources must be allocated effectivelly. Research and monitoring activities must also be allocated with sensitivity to local priorities and limitations. Protected areas must be managed to protect the values they contain, not provide statistics. Managers should only be required to collect data that are useful to them in ways that they understand. Research ought not be conducted at the cost of failing to halt the overwhelming threats now facing many conservation areas.Threats must be identified and priorities revisited, but the costs and responsibilities for generating such information must be allocated with care. (YS)